Pendidikan Agama Kristen Berbasis Pemuridan di Perguruan Tinggi (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2021)
This article aims to find out effective discipleship strategies in higher education through Christian Religious Education, using descriptive qualitative methods. The Christian Religious Education Course which weighs only 2-3 credits per semester does not allow for effective, efficient and productive discipleship. So, discipleship must be carried out outside the classroom. In the classroom only to deliver lecture material and continued outside the classroom in the form of small groups. Indeed, lecturers are very important to empower senior students to guide juniors so that they take root, grow and bear fruit in Christ.